A systematic review of Political Skill research with bibliometric indicators - Castillo Alarcón, Rony; Cabrera Reyes, Marcelo; Cisterna Aravena, Cristian (RAN - Revista Academia & Negocios, 2023)
Purpose: To provide an informative overview of political skill research production, competence with the potential to refine social influence and generate business networks. Design/methodology: Systematic literature review with bibliometric techniques of publications in political skill in Web of Science (WoS), from 1975 to date. Results: The most significant authors, publications, articles and journals in political skill are exposed, providing an understanding of their production as a resource for social effectiveness. Implications: To highlight in the business world the value coming from research on political skill to promote the development of competencies in commercial representatives of companies, a more robust relationship with customers and a better understanding of the competitive scenario. Originality: To contribute in an unprecedented way with a guide that summarizes and orients with respect to research in political skill and encourages the incorporation of this resource for the future performance of firms.